Traditional Lease and Ideal Lease: The Subtle Meanings of Lease Length - Thongsukplang Hansasooksin, Suwadee (Journal of Architectural/Planning Research and Studies (JARS), 2015)
Despite the same few components of ground leases, an important variable that differentiates traditional lease from ideal lease is the length of leasehold term. Ground leases in Thailand can be granted in compliance with two laws: the Civil and Commercial Code, and the Hire Act of Immovable Property for Commerce and Industry B.E. 2542 (1999). While the former is the traditional lease releasing the maximum term of the leasehold at 30 years, the latter is the recent law extending the period of lease to 50 years. Nonetheless, there have been many attempts to extend the ideal lengths of lease to 90 – 99 years. Each length of lease, either the traditional or the ideal one, could be considered as a magic number. The backgrounds of such numbers illustrate not only the movement of the market altered by socio-economic circumstances, but also the tension between the traditional lease and the ideal lease which is based on longer time periods. However, it is interesting in that a leasehold agreement is still generally based on the 30-year leasehold tenure. Thus, the attention to leases in this paper is paid to the determination and application of length term, as well as the subtle meaning of each length of lease.